THE FOUNDATIONS OF CONCEPTUAL AND TERMINOLOGICAL APPARATUS OF CRYPTOLOGY - ZagatskaN. (Journal of Information Technologies in Education (ITE), 2015)
Formation of cryptology as a science has necessitated the formation need of its own conceptual apparatus of the discipline with its inherent characteristics. The problem is the lack of up to date generally accepted interpretation of concepts and terms which studying is the basis for successful mastering the discipline’s educational material by the students. One of the main tasks to be solved in the studying process of this discipline is to provide a careful examination of the theoretical foundations by students that will facilitate the formation of professional competencies necessary to understand the general principles of cryptographic systems. The article studies the conceptual and terminological cryptology apparatus. The comparative analysis of the science’s concept on the basis of national and foreign professional sources, explanatory and specialized dictionaries, legal and legislative acts of Ukraine in the field of cryptographic data protection has been hold. The article describes the fundamental and derivative terms due to their structural and logical connections. The classification of cryptosystems is proposed: key features, type and encrypting technology. An attempt to clarify the common terminology of the science is made that will contribute the future specialists in computer science to master it.